2017
DOI: 10.1111/1756-185x.13117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethnicity on clinical presentation and risk of antiphospholipid syndrome in Roma and Caucasian patients with systemic lupus erythematosus: a multicenter cross‐sectional study

Abstract: Prevalence and risk of APS were significantly higher in Roma SLE patients. Furthermore, Roma patients had a significantly higher prevalence of abortions and a non-significant higher prevalence of fetal deaths and thrombotic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…[ 2 ] As stated in other studies, research concerning SLE in pregnant women have often been limited to a particular ethnic group, or most of the time to a specific region. [ 3 , 4 ] Therefore, to generalize this issue, Bundhun et al clearly demonstrated the impact of SLE on maternal and fetal outcomes through a meta-analysis including various studies from different parts of the globe and included studies which were published between the years 2001 and 2016. [ 5 ] The authors clearly showed the associated adverse events with this life threatening disease throughout pregnancy and stated that special care and treatment should be provided to those women to minimize the risk of unfavorable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] As stated in other studies, research concerning SLE in pregnant women have often been limited to a particular ethnic group, or most of the time to a specific region. [ 3 , 4 ] Therefore, to generalize this issue, Bundhun et al clearly demonstrated the impact of SLE on maternal and fetal outcomes through a meta-analysis including various studies from different parts of the globe and included studies which were published between the years 2001 and 2016. [ 5 ] The authors clearly showed the associated adverse events with this life threatening disease throughout pregnancy and stated that special care and treatment should be provided to those women to minimize the risk of unfavorable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of our study is that SLE patients were, on average, older than controls (40 years vs. 34 years), which could have affected the prevalence of periodontitis; however, we think that the age group where it occurs the difference does not affect this frequency measurement. Another potential limitation is that the SLE group could not be representative of general SLE patients from a Caucasian population, due to a selection bias, but the demographic characteristics of this group are similar to the ones of other previously published studies with larger samples 6,37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Progress has been made in identifying the genes underlying JIA susceptibility, but only a few studies have shown the identification of environmental factors to be a trigger of the immunological abnormalities of JIA. Most of these studies discussed the connection between early life infection, maternal smoking, and autoimmune disease, but ethnicity was involved in only very few of them [23,24]. In 2018 Manzano-Gamero et al found a higher risk of antiphospholipid syndrome in Roma patients diagnosed with systemic lupus erythematodes [25].…”
Section: Discussionmentioning
confidence: 99%